Biomarkers Associated With Aortic Valve Calcification: Should We Focus on Sex Specific Processes? - Peeters, Frederique E. C. M.; Dudink, Elton A. M. P.; Weijs, Bob; Fabritz, Larissa; Chua, Winnie; Kietselaer, Bas L. J. H.; Wildberger, Joachim E.; Meex, Steven J. R.; Kirchhof, Paulus; Crijns, Harry J. G. M.; Schurgers, Leon J. (Frontiers in Cell and Developmental Biology, 2020)
Objective: Circulating biomarkers are useful in detection and monitoring of cardiovascular diseases. However, their role in aortic valve disease is unclear. Mechanisms are rapidly elucidated and sex differences are suggested to be involved. Therefore, we sought to identify biomarkers involved in aortic valve calcification (AVC) stratified by sex. Methods: Blood samples of 34 patients with AVC (without further overt cardiovascular disease, including absence of hemodynamic consequences of valvular calcification) were compared with 136 patients without AVC. AVC was determined using computed tomography calcium scoring. Circulating biomarkers were quantified using a novel antibody-based method (Olink Proseek Multiplex Cardiovascular Panel I) and 92 biomarkers were compared between patients with and without AVC. Results: In the overall population, Interleukin-1 Receptor Antagonist and pappalysin-1 were associated with increased and decreased odds of having AVC. These differences were driven by the male population (IL1RA: OR2.79(1.16-6.70),p=0.022; PAPPA: OR 0.30(0.11-0.84),p=0.021). Furthermore, TNF-related activation-induced cytokine and fibroblast growth factor-23 were associated decreased odds of having AVC, and monocyte chemotactic protein-1 was associated with increased odds of having AVC (TRANCE: OR0.32(0.12-0.80),p=0.015; FGF23: OR0.41(0.170-0.991),p=0.048; MCP1: OR2.64(1.02-6.81),p=0.045). In contrast, galanin peptides and ST2 were associated with increased odds of having AVC in females (GAL: OR12.38(1.31-116.7),p=0.028; ST2: OR13.64(1.21-153.33),p=0.034). Conclusions: In this exploratory study, we identified biomarkers involved in inflammation, fibrosis and calcification which may be associated with having AVC. Biomarkers involved in fibrosis may show higher expression in females, whilst biomarkers involved in inflammation and calcification could associate with AVC in males.